Hubungan antara Minat Penggunaan Instagram sebagai Media Belajar Mandiri dengan Prestasi Belajar Mahasiswa Program Studi Pendidikan Bahasa Arab UIN Sunan Kalijaga angkatan 2022 - Maulana, Azhar; Hamdan Hadi Purnomo (Mahira: Journal of Arabic Studies & Teaching, 2024)
This research aims to: 1) To find out the interest of the ArabicLanguage Education Department students of the class of 2022 inusing Instagram as a means of learning Arabic independently. 2) Tofind out the Arabic language learning achievement of the studentsof the Arabic Language Education Department, Class of 2022. 3) Tofind out the relationship between the interest of the ArabicLanguage Education Department students of the class of 2022 inusing Instagram as a means of learning the Arabic languageindependently and the achievement of Arabic language learning.This research uses the quantitative method and includes a type of correlation research, where the  researchers collect data in this study through questionnaires and documentation. The research tools were guiding questionnaires and cumulative student questionnaires and documentation. The data obtained are then reprocessed in the form of numbers by the researchers and the results are interpreted in the form of explanations. The results of the study indicate that students' interest in using Instagram as a means of independent Arabic language learning is categorized as average with 68.60%, students' achievement in learning is categorized as average with 76.74%, and there is a linear relationship between interest in using Instagram as a means of independent Arabic language learning with Arabic language learning achievement for Arabic language education students at Sunan Kalijaka University Class of 2022 with a correlation coefficient of 0.222 and significance of 0.040.